2018
DOI: 10.1111/gcb.14433
|View full text |Cite
|
Sign up to set email alerts
|

Pivotal roles of environmental sensing and signaling mechanisms in plant responses to climate change

Abstract: Climate change reshapes the physiology and development of organisms through phenotypic plasticity, epigenetic modifications, and genetic adaptation. Under evolutionary pressures of the sessile lifestyle, plants possess efficient systems of phenotypic plasticity and acclimation to environmental conditions. Molecular analysis, especially through omics approaches, of these primary lines of environmental adjustment in the context of climate change has revealed the underlying biochemical and physiological mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 154 publications
(475 reference statements)
0
20
0
Order By: Relevance
“…The accumulated impact of human life on our planet over the past several decades, and in particular the industrial revolution, resulted in a constant increase in greenhouse gas production (mainly CO 2 ) caused by the burning of fossil fuels ( Figure 1A; www.ipcc.ch/) [1][2][3][4][5][6][7][8][9]. The accumulation of CO 2 in the atmosphere traps the IR radiation emitted from the surface of the Earth following absorption of sunlight and heats our planet, driving an alarming trend of continual increase in global surface and ocean temperatures, termed global warming ( Figure 1A; www.ipcc.ch/, https://ourworldindata.org/owid-grapher, www.eea.europa.eu/) [1][2][3][4][5][6][7][8][9].…”
Section: The Diminishing Resources and Deteriorating Environmental Comentioning
confidence: 99%
“…The accumulated impact of human life on our planet over the past several decades, and in particular the industrial revolution, resulted in a constant increase in greenhouse gas production (mainly CO 2 ) caused by the burning of fossil fuels ( Figure 1A; www.ipcc.ch/) [1][2][3][4][5][6][7][8][9]. The accumulation of CO 2 in the atmosphere traps the IR radiation emitted from the surface of the Earth following absorption of sunlight and heats our planet, driving an alarming trend of continual increase in global surface and ocean temperatures, termed global warming ( Figure 1A; www.ipcc.ch/, https://ourworldindata.org/owid-grapher, www.eea.europa.eu/) [1][2][3][4][5][6][7][8][9].…”
Section: The Diminishing Resources and Deteriorating Environmental Comentioning
confidence: 99%
“…This would result in a different perception and signalization between sides; for example, stomata of Gossypium barbadense (L.) have distinct sensitivity to light between sides linked with different pigment contents (Lu, Quiñones, & Zeiger, 1993). A different sensitivity between sides would lead to a diversity of gene expression (see Bigot et al, 2018), and element content in the guard cells, which may be a part of what we observed. A stronger gene expression on the adaxial side might be seen as the result of a more extreme condition on the side facing the light source.…”
Section: Leaf Side and Time Of Day Shape Guard Cell Element Contentmentioning
confidence: 77%
“…Previously reported thermal and irradiance gradients between leaf surfaces of a few degrees (Buckley, John, Scoffoni, & Sack, ; Clum, ; Sheriff, ) could result in different perceived environmental conditions between leaf sides (e.g., light, VPD, and temperature), prompting different stomatal control, as was found on poplar clones in response to a change in light and VPD (Ceulemans, Hinckley, & Impens, ; Pallardy & Kozlowski, ). Differences in the intensity and nature of perceived stresses, such as evaporative demand, light, and heat (Urban, Ingwers, McGuire, & Teskey, ) may induce a distinct conjugation of stress between sides, which may affect the synergic or antagonistic response to environmental cues (Bigot et al, ). This would result in a different perception and signalization between sides; for example, stomata of Gossypium barbadense (L.) have distinct sensitivity to light between sides linked with different pigment contents (Lu, Quiñones, & Zeiger, ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has also demonstrated that chloroplast-localized SDP, which affects rRNA processing in chloroplasts under normal conditions, has positive effects on salt, heat, freezing, or UV stress tolerance, as it influences the stress-responsive genes in the nucleus [ 117 ]. Beyond organelles, it will be of great interest to investigate how nCMRBP-mediated organellar retrograde signaling (ORS) influences the reprogramming of the expression of stress-responsive nuclear genes, and the organellar and nuclear epigenetic modifications for stress priming and memory [ 101 , 118 , 119 , 120 , 121 ]. Although the study of organellar proteomics and metabolomics is far behind than those in the nucleus and cytoplasm, recent studies emphasize the importance of homeostasis between the nucleus and organelles in plant acclimation to environmental changes [ 122 , 123 , 124 , 125 ].…”
Section: Physiological Functions Of Ncmrbps In Abiotic Stress Respmentioning
confidence: 99%